2016
DOI: 10.1002/ejic.201600775
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Functionizable Tetracarbonyl(phenylpyridine)manganese(I) Complexes as CO‐Releasing Molecules: A Direct Suzuki–Miyaura Cross‐Coupling on a Thermally Stable CO‐RM

Abstract: A new class of carbon monoxide-releasing molecules (CO-RMs) are reported based on a previously known tetracarbonyl phenylpyridine manganese(I) motif. A pre-functionalized CO-RM undergoes a direct Pd-catalysed Suzuki-Miyaura crosscoupling with phenylboronic acid to give a π-extended threering CO-RM. Cross-coupling conditions were modified to allow coupling of a morpholine-containing boronic acid on to a CO- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…425–325 nm. On the basis of previous results, irradiation within this wavelength range is known to result in CO loss. DFT was employed to rationalize the observed spectra.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…425–325 nm. On the basis of previous results, irradiation within this wavelength range is known to result in CO loss. DFT was employed to rationalize the observed spectra.…”
Section: Resultsmentioning
confidence: 69%
“…Complex [ 1a ] was first described by Bruce in 1975 and is readily prepared from the reaction of 2-phenylpyridine with [Mn­(CH 2 Ph)­(CO) 5 ] . In previous studies, we have shown that [ 1a ], and its derivatives with modified 2-phenylpyridine groups (Figure ), act as photochemically activated CO-releasing molecules (photoCO-RMs). Irradiation (λ = 400 nm) results in loss of up to three CO ligands as measured by the conversion of deoxymyoglobin to carboxymyoglobin. Furthermore, time-resolved spectroscopy has demonstrated that photolysis (λ = 355 nm) of [ 1a ] in the presence of catalytically relevant substrates such as alkynes, alkenes, and isocyanates can be used to initiate CO loss and observe the subsequent states involved in the C–C bond formation event which underpins Mn-catalyzed reactions .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactions given in Scheme are both believed to involve manganacycle 4 . , We identified that the use of real-time infrared spectroscopic analysis (in situ IR on the second time scale), in operando, is useful for probing the different manganese carbonyl species formed during the C–H bond activation reactions, yielding qualitative information about manganese carbonyl speciation and quantitative kinetic data. Use of IR spectroscopic analysis for studying transient manganese carbonyl species has been validated in our previous studies . For this mechanistic study, a Mettler-Toledo ReactIR instrument (IC10) with a Si probe was used (1 min scans, ± 4 cm –1 ) to monitor changes in the manganese carbonyl IR bands in real time.…”
Section: Resultsmentioning
confidence: 99%